EFL STUDENTS’ ATTITUDE TOWARD ENGLISH LANGUAGE LEARNING - Novi Dwi Yuliani; Lailatun Najmiah; Beny Hamdani; Bambang Widi Pratolo (Journey: Journal of English Language and Pedagogy, 2023)
Attitude revealed as a serious issue in foreign language learning. It is a way for someone to behave on a situation, whether like or dislike, good or bad, and positive or negative. This study investigates the EFL students’ attitude toward English language learning. This study aims to identify the students’ attitude toward English language learning in three aspects; they are behavior, cognitive and affective. A close-ended questionnaire was distributed to 10 students of post-graduate Program of Ahmad Dahlan University. Then, an interview was also conducted with three students as representatives from every aspect of attitude. The results of this qualitative study showed a positive attitude toward English language learning in three aspects; behavioral, cognitive, and affective. Furthermore, the result also showed the influence of attitude toward students’ achievement and motivation in English language learning.